Pengaruh Pemberian Seledri (Apium Graveolens L.) Terhadap Penurunan Hiperkolesterolemia Pada Lansia Di Panti Wreda Darma Bhakti Kasih Surakarta - Hartono Hartono; Siti Handayani (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract: Celery, Hypercholesterolemia. Dyslipidemia is a lipid metabolic disorder characterized by elevated total cholesterol, LDL cholesterol, triglycerides above normal values and a decrease in HDL cholesterol. In traditional medicine, herb celery has been used as a medicine to lower cholesterol levels because of the content of unsaturated fatty acids in celery plants. The purpose of this study was to determine the effect of celery extract on the decrease of hypercholesterolemia in Elderly. Type The design of this study is quasi experimental with one group pre test post test design. The population in this study were all elderly in Panti Wreda Darma Bhakti Kasih Surakarta in 2016 with total sampling that is all respondents of the research after examination total cholesterol, triglycerides and LDL at Parahita Diagnostic Center Surakarta Laboratory with high cholesterol result of 29 people. Result of Analyst Paired t-test Total Cholesteol levels before and after giving Celery extract in Elderly showed P value 0.029 which means there is influence between before and after giving Celery extract. Result of Willcoxon test analysis of Triglyceride level before and after giving Celery extract in Elderly obtained P value: 0,414 which means no influence between before and after giving Celery extract. The results of Willcoxon test analysis of LDL levels before and after giving Celery extract in Elderly obtained P value: 0,102 which means no influence between before and after giving extract Celery